PEMANFAATAN LIMBAH KULIT JAGUNG SEBAGAI BAHAN PEMBUATAN BAKI HANTARAN PERNIKAHAN (Beauty and Beauty Health Education, 2021)
Utilization of corn husk waste in the Boyolali area is still not optimal, causing a build up of the amount of organic waste in the Boyolali Regency area. According to data from the Central Statistics Agency for Boyolali Regency 2019, the corn harvest reached 25,984 kg. To optimize the selling value and artistic value, the waste is used to make handicrafts, one of which is a wedding gift tray. The purpose of the study was to determine the level of validity of the wedding delivery tray and to determine the level of preference for the wedding delivery tray. The research method used is research and development. Methods of data collection using the method of documentation and observation. Data collection using a questionnaire. The product validity was carried out by 3 expert panelists and the preference test was carried out by 15 untrained panelists. The analysis technique in this research uses descriptive percentage. The results of the validity test state that the delivery tray is valid with the average of all products above 90.00% so that it is feasible to do research. The results of the preference test stated that the products A1 and A4 were the most preferred with an average of 93.00%.